2001
DOI: 10.1007/bf01171220
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of wood after moisture conditioning

Abstract: Abstrael Some properties of wood (hinoki: Charnaecyparis obtusa) moisture-conditioned by an adsorption process from a dry state and by two desorption processes (from a water-saturated state and from a state with a moisture content slightly below the fiber saturation point) were investigated. The moisture contents of wood conditioned by the adsorption process and by the desorption process continued to approach to one another for the moisture-conditioning period of over 50 weeks. Accordingly, sorption hysteresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 4 publications
2
15
0
1
Order By: Relevance
“…It is confirmed that at room temperature, when MC is over the fiber saturation point (FSP), the MC variation has little influence on wood MOE; however, when it is below the FSP, an increase in MC caused a decrease in wood MOE, the relationship between which was that MOE increased 1.5% when the MC decreased by 1% (Ishimaru et al 2001;GB/T 1936GB/T .2 2009. Thus, when MC change was considered, the increases in MOE of air-dried one after each treatment were 3.52%, 5.62%, 1.98%, and 3.00%, respectively, while that of the oven-dried one were 4.70%, 3.63%, 5.68%, and 5.53%, respectively.…”
Section: Moe Of One To Four Cyclic Treatmentsmentioning
confidence: 71%
“…It is confirmed that at room temperature, when MC is over the fiber saturation point (FSP), the MC variation has little influence on wood MOE; however, when it is below the FSP, an increase in MC caused a decrease in wood MOE, the relationship between which was that MOE increased 1.5% when the MC decreased by 1% (Ishimaru et al 2001;GB/T 1936GB/T .2 2009. Thus, when MC change was considered, the increases in MOE of air-dried one after each treatment were 3.52%, 5.62%, 1.98%, and 3.00%, respectively, while that of the oven-dried one were 4.70%, 3.63%, 5.68%, and 5.53%, respectively.…”
Section: Moe Of One To Four Cyclic Treatmentsmentioning
confidence: 71%
“…This explanation cannot be applied to crystalline cellulose as the cellulose chains packed into a crystallite are already in close contact with each other. Ishimaru et al (2001) suggested an alternative mechanism: coupling (intramolecular hydrogen bonding) of hydroxyl groups on crystallite surfaces during drying, thereby leaving fewer sites for subsequent adsorption of moisture. We sought evidence for these hypothetical changes on cellulose crystallite surfaces by wide angle X-ray scattering (WAXS) techniques.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that a decrease in moisture content below the FSP significantly influences the mechanical properties of the wood, whereas above the FSP, variations in moisture content have very little effect. Furthermore, it has been further revealed that different mechanical properties of wood have different sensitivities to a change in MC (Green et al 1999;Ishimaru et al 2001;Sudijono et al 2004). Specifically, data in the United States Wood Handbook indicates that the longitudinal tensile strength of wood decreases 16.7% from an air-dried state (MC 12%) to a saturated state; other properties that decrease include bending modulus (23.7%), shearing strength parallel to the grain (30.0%), and compressive strength parallel to the grain (42.5%).…”
Section: Introductionmentioning
confidence: 99%